Proses Transformasi: Tinjauan Literatur pada Kawasan Industri Konvensional Menuju Kawasan Industri Berbasis Eco-Smart - Syafrijon, Syafrijon (Jurnal Talenta Sipil, 2024)
Industrial estates contribute to the economy, but conventional estates can damage the environment. Green technology innovation, especially bio-based and renewable energy, is the solution. Investments in green technology support both the environment and the economy. And the 4th industrial revolution emphasizes sustainable manufacturing. So Eco-Smart based industrial estates with a focus on sustainability are the transformation solution. To knowing the framework for the transformation of conventional industrial estates to eco-smart based industrial estates and its impact on the industrial estate. This study used a literature review method that involved surveying various sources such as journals, books, documentation, internet, and literature relevant to the object of research. PICOT framework was used to search for international online journals with the keywords “Transformation Process, Conventional Industrial Estates, Eco-Smart Industrial Estates. The findings reveal that transforming industrial areas into eco-smart ones requires leadership, community participation and government financial support. Successful initiatives such as the Border Area Development Program in Saboo village, India, and China's progressive policies reflect a commitment to sustainable urbanization. The transformation process involves zone selection, context analysis, community participation, and optimization of Industrial Ecology (IE) and Industrial Symbiosis (IS). By reducing pollutant emissions, improving environmental quality, and contributing to urban green space construction, this transformation brings positive impacts in green innovation, industrial structure optimization, and environmental regulation strengthening, especially in eastern and northern cities with abundant human and financial resources.The transformation of conventional industrial estates to eco-smart industrial estates has resulted in positive impacts in innovation, improved environmental quality, and contributions to urban green spaces as well as financial improvements for the region. Top of Form